Evaluation of scores of the 33rd and 34th Junior European Championships in Men`s Artistic Gymnastics - Kosova, M. K.; Kosova, S. (European Journal of Human Movement, 2021)
To determine the effects of difficulty (D), execution (E), and total score of the apparatus on the all-around total score, and compare the scores of the 33rd and 34th Junior European Championships in Men`s Artistic Gymnastics (JECMAG). The data of the study are the all-around scores of the final of the 33rd (2018) and 34th (2020) JECMAG. The all-around total score (AATS), apparatus total score, D and E score of each apparatus were evaluated. A multiple regression was run to predict AATS2018 from the total score of the vault, pommel horse, horizontal bar, floor exercise, parallel bars, and AATS2020 from the parallel bars (p<.001). Multiple regression analysis was run to predict AATS2018 from scores of vault D, pommel horse D, vault E, horizontal bar E, horizontal bar D, pommel horse E, floor exercise D scores and AATS2020 from parallel bars D, parallel bars E, pommel horse E scores (p<.001). In the 34th JECMAG, there were significant decreases in AATS and some apparatus scores compared with the 33rd JECMAG. Although the effect of apparatus scores changed according to the competition dynamics, the most important apparatus seemed to be the vault (2018) and parallel bars (2020). It can be concluded that D scores were better predictors than E scores. Coaches can take these findings into account when determining competition strategies.